The crosslinks between ferroptosis and autophagy in asthma - Lv, Xiaodi; Tang, Weifeng; Qin, Jingjing; Wang, Wenqian; Dong, Jingcheng; Wei, Ying (Frontiers in Immunology, 2023)
Autophagy is an evolutionarily conserved cellular process capable of degrading various biological molecules and organelles via the lysosomal pathway. Ferroptosis is a type of oxidative stress-dependent regulated cell death associated with the iron accumulation and lipid peroxidation. The crosslinks between ferroptosis and autophagy have been focused on since the dependence of ferroptosis on autophagy was discovered. Although the research and theories on the relationship between autophagy and ferroptosis remain scattered and fragmented, the crosslinks between these two forms of regulated cell death are closely related to the treatment of various diseases. Thereof, asthma as a chronic inflammatory disease has a tight connection with the occurrence of ferroptosis and autophagy since the crosslinked signal pathways may be the crucial regulators or exactly regulated by cells and secretion in the immune system. In addition, non-immune cells associated with asthma are also closely related to autophagy and ferroptosis. Further studies of cross-linking asthma inflammation with crosslinked signaling pathways may provide us with several key molecules that regulate asthma through specific regulators. The crosslinks between autophagy and ferroptosis provide us with a new perspective to interpret and understand the manifestations of asthma, potential drug discovery targets, and new therapeutic options to effectively intervene in the imbalance caused by abnormal inflammation in asthma. Herein, we introduce the main molecular mechanisms of ferroptosis, autophagy, and asthma, describe the role of crosslinks between ferroptosis and autophagy in asthma based on their common regulatory cells or molecules, and discuss potential drug discovery targets and therapeutic applications in the context of immunomodulatory and symptom alleviation.